Pictorial keys to the sections, groups, and species of the Aedes (Finlaya) in the Afrotropical Region (Diptera: Culicidae) - Huang, Yiau-Min; Rueda, Leopoldo M. (Zootaxa, 2017)
Eight species of the subgenus Finlaya Theobald, genus Aedes Meigen, in the Afrotropical Region are treated in pictorial keys based on diagnostic morphological features. Images of the diagnostic morphological structures of the adult thorax, leg and wing are included.